PERTUMBUHAN DAN LAJU EKSPLOITASI IKAN KEMBUNG (Rastrelliger spp.) DI PERAIRAN SELAT MALAKA PROVINSI SUMATERA UTARA The Growth and Exploitation Rates ofMackerelFish (Rastrelliger spp.) in Malacca Strait, Medan Belawan District, North Sumatera Province - Yuli Wulandari; Budi Utomo; Desrita Desrita (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2017)
Mackerel Fish (Rastrelliger spp.) is one type of economic fish in important for the community, this type is found in the waters of the Strait of Malacca. This study has objectives on accesing growth and exploitation rates of Mackerel Fish in Malacca Strait, North Sumatera Province. This study was held in three months, from March to May 2017. Data analysis used the ELEFAN I method (Electronic Lenght Frequencys Assesment Tool) by using FiSAT II (FAO-ICLARM Fish Stock Assesment Tool) software. The samples of Mackerel Fish obtained as much 361 tail. The growth pattern of Mackerel Fish is negative allometric. The range of condition factor are 0,602 – 1,294. The range of length frequency distribution are 175 – 182 mm. Based on the growth equation of Von Bertalanffy Mackerel Fish obtained in the waters of the Straits of Malacca is Lt = 217,351-e-0,75(t+0,015) which means the asymptothed length (L∞) of Mackerel Fish 217,35 growth coefficient (K) of 0,75 per year and the theoretical age (t0) Mackerel Fish that is equal to -0,015. Total mortality (Z) of Mackerel Fish of 2,837 per year.Estimation of natural mortality rate (M) of Mackerel Fish of 0,891 per year and mortality due to catch (F) of 1,946 per year. So that the result of alleged exploitation rate of 0,68 per year.Keywords: Growth, Mortality, Exploitation Rates, Rastrelliger spp, Malacca Strait